2021
DOI: 10.1002/er.7340
|View full text |Cite
|
Sign up to set email alerts
|

Performance evaluation of a thermoelectric generator‐coupled composite phase change material for intermittent aerodynamic heat sources

Abstract: Thermoelectric generator (TEG) can utilize intermittent temperature fluctuations of the aircraft's fuselage to provide power for wireless structural health monitoring systems. In this article, a novel phase change material (PCM)-TEG system of integrating PCM with TEG for improving the output performance was reported. The proposed system was almost adiabatic with the external environment, which effectively avoided heat exchange with the internal environment of the aircraft. High-performance paraffin/expanded gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…Despite significant efforts invested in developing high-performance TE devices with rigid Bi 2 Te 3 -based TE pillars and flexible interconnects, the low thermal conductivity of encapsulation materials, rigid and bulky heatsinks, and interfacial mismatching between hard and soft components remain the major challenges of the dynamic performance of flexible TE devices. Despite the fact that high thermal conductive materials such as Ag, AlN, alumina, graphene, and liquid metals have been embedded into elastomers to improve the heat conduction and dissipation of device encapsulation, the maximum thermal conductivities of such composites are still approximately 1 W/(m K), comparing much smaller than pure metals and graphene. Previous works have demonstrated using phase-change materials (PCMs) such as n -octadecane (C 18 H 38 ) and paraffin as heat absorbers to maintain a relatively low temperature on the hot side. However, the above PCMs possess a melting temperature of 28 °C, suggesting their incompetence to serve as an effective heatsink in hot weather.…”
Section: Introductionmentioning
confidence: 99%
“…Despite significant efforts invested in developing high-performance TE devices with rigid Bi 2 Te 3 -based TE pillars and flexible interconnects, the low thermal conductivity of encapsulation materials, rigid and bulky heatsinks, and interfacial mismatching between hard and soft components remain the major challenges of the dynamic performance of flexible TE devices. Despite the fact that high thermal conductive materials such as Ag, AlN, alumina, graphene, and liquid metals have been embedded into elastomers to improve the heat conduction and dissipation of device encapsulation, the maximum thermal conductivities of such composites are still approximately 1 W/(m K), comparing much smaller than pure metals and graphene. Previous works have demonstrated using phase-change materials (PCMs) such as n -octadecane (C 18 H 38 ) and paraffin as heat absorbers to maintain a relatively low temperature on the hot side. However, the above PCMs possess a melting temperature of 28 °C, suggesting their incompetence to serve as an effective heatsink in hot weather.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the integration of PCMs in TEG systems, most of the studies conducted so far consider the PCM as an external component of the thermoelectric generator, which results in a modest enhancement of the final thermoelectric performance [ 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 ]. No studies have reported the incorporation of PCMs within the thermoelectric material, which can potentially improve the heat transport and performance of the final device.…”
Section: Introductionmentioning
confidence: 99%
“…At present, the TEG technique has already been employed in a variety of space missions, like the Transit 4A satellite, 9 Curiosity Mars rover, 9 Galileo spacecraft, 10 New Horizons space probes, 11 and Cassini spacecraft 11 and for hypersonic engineering, it is also considered as one the most promising TM techniques and attracts lots of research attentions. [12][13][14][15][16][17][18][19][20][21][22] The TPS with integrated TEGs is described as "holds the potential to harvest free energy and save weight by reducing onboard power systems" in the NASA's Technology Area Roadmap 14-Thermal Management Systems. 23 A TEG is usually composed of a couple of P-and N-type TE material legs, which can convert the heat into electric energy under certain temperature difference based on the so-called Seebeck effect.…”
Section: Introductionmentioning
confidence: 99%